2011
DOI: 10.1111/j.1600-0560.2011.01701.x
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidosis cutis dyschromica: a rare pigmentary disorder

Abstract: Amyloidosis cutis dyschromica represents a rare type of primary cutaneous amyloidosis with few reported cases worldwide. It is characterized by asymptomatic, generalized hyperpigmentation with intermingled hypopigmented macules without atrophy or telangiectasia. We report herein a 19-year-old female who developed this pigmentary abnormality at 4 years of age. Her aunt and great grandfather also had similar skin pigmentation. An unusual finding in our patient was the presence of papules in addition to character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…X‐linked reticulate pigmentary disorder with systemic manifestations (XLPDR, OMIM 301220) was first described by Partington et al [] and was originally called familial cutaneous amyloidosis or X‐linked cutaneous amyloidosis because of similarity with amyloidosis cutis dyschromica [Garg et al, ] showing the deposition of amyloid‐like material in the skin of affected adults. XLPDR is a rare disease and only five families [Partington et al, ; Adès et al, ; Anderson et al, ; Mégarbané et al, ; Fernandez‐Guarino et al, ] and one sporadic case [Kim et al, ] have been reported till now.…”
Section: Introductionmentioning
confidence: 99%
“…X‐linked reticulate pigmentary disorder with systemic manifestations (XLPDR, OMIM 301220) was first described by Partington et al [] and was originally called familial cutaneous amyloidosis or X‐linked cutaneous amyloidosis because of similarity with amyloidosis cutis dyschromica [Garg et al, ] showing the deposition of amyloid‐like material in the skin of affected adults. XLPDR is a rare disease and only five families [Partington et al, ; Adès et al, ; Anderson et al, ; Mégarbané et al, ; Fernandez‐Guarino et al, ] and one sporadic case [Kim et al, ] have been reported till now.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these well‐described forms of primary cutaneous amyloidosis, several atypical forms have been reported. These include the poikiloderma‐like, bullous, vitiliginous, anosacral amyloidosis and amyloidosis cutis dyschromica …”
Section: Discussionmentioning
confidence: 99%
“…The etiology of non‐familial primary cutaneous amyloidosis is unknown but has been hypothesized to be multifactorial, including frictional, environmental (e.g., ultraviolet radiation) epidermal damage, and immunological factors. There are no disease associations in amyloidosis cutis dyschromica, and the diagnosis is made with a clinicohistological correlation …”
Section: Discussionmentioning
confidence: 99%
“…Macular amyloidosis presents with corrugated hyperpigmentation, particularly involving the upper trunk, while lichen amyloidosus prototypically presents with monomorphous hyperkeratotic and lichenified papules that favor the shins. Amyloidosis cutis dyschromica presents with diffuse dyspigmentation, small white macules, and occasional small papules …”
Section: Acknowledgementmentioning
confidence: 99%
“…Amyloidosis cutis dyschromica presents with diffuse dyspigmentation, small white macules, and occasional small papules. 2,5 Histopathologically, these entities are all typified by the presence of amorphous, amphophilic globular material deposited in the papillary dermis, and the most abundant amyloid is typically associated with lichen amyloidosus. It can be challenging to confirm the presence of keratinocyte-derived amyloid by traditional special staining techniques.…”
mentioning
confidence: 99%